Diglossia and identity in Northeast Thailand: Linguistic, social, and political hierarchy. (February 2014) - Alexander, Saowanee T.; McCargo, Duncan
<x xml:space="preserve">Abstract</x> The paper explores diglossic relations between Central Thai and phasa isan, a variety officially known as a dialect of Thai, but linguistically close to Lao. Phasa isan is spoken by almost one‐third of Thailand's population but its speakers in the Northeast are often stigmatized as uneducated and backward. We conducted field research mainly among university students in Ubon Ratchathani, a northeastern border province, by drawing upon data from survey questionnaires, reflective essays, interviews, and field observations. The findings suggest a transitional diglossic relationship in which Central Thai is the High and phasa isan the Low variety. These relationships are discussed in terms of nationalism, social hierarchy, and language maintenance and shift.